Indications and expectations for neuropsychological assessment in epilepsy surgery in children and adults: Report of the ILAE Neuropsychology Task Force Diagnostic Methods Commission: 2017 - 2021 Neuropsychological assessment in epilepsy surgery - Baxendale, Sallie; Wilson, Sarah J.; Baker, Gus A.; Barr, William; Helmstaedter, Christoph; Hermann, Bruce P.; Langfitt, John; Reuner, Gitta; Rzezak, Patricia; Samson, Séverine; Smith, Mary-Lou (Epileptic disorders, 2019)
In our first paper in this series (Epilepsia 2015; 56(5): 674-681), we published recommendations for the indications and expectations for neuropsychological assessment in routine epilepsy care. This partner paper provides a comprehensive overview of the more specialist role of neuropsychological assessment in the pre and postoperative evaluation of epilepsy surgery patients. The paper is in two parts. The first part presents the framework for the mandatory role of neuropsychologists in the presurgical evaluation of epilepsy surgery candidates. A preoperative neuropsychological assessment should be comprised of standardised measures of cognitive function in addition to wider measures of behavioural and psychosocial function. The results from the presurgical assessment are used to: (1) establish a baseline against which change can be measured following surgery; (2) provide a collaborative contribution to seizure characterization, lateralization and localization; (3) provide evidence-based predictions of cognitive risk associated with the proposed surgery; and (4) provide the evidence base for comprehensive preoperative counselling, including exploration of patient expectations of surgical treatment. The second part examines the critical role of the neuropsychologist in the evaluation of postoperative outcomes. Neuropsychological changes following surgery are dynamic and a comprehensive, long-term assessment of these changes following surgery should form an integral part of the postoperative follow-up. The special considerations with respect to pre and postoperative assessment when working with paediatric populations and those with an intellectual disability are also discussed. The paper provides a summary checklist for neuropsychological involvement throughout the epilepsy surgery process, based on the recommendations discussed.